2016
DOI: 10.1007/s10534-016-9925-5
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin 2 alleviates iron toxicity by facilitating hypoferremia of inflammation and limiting catalytic iron generation

Abstract: Iron is an essential transition metal ion for virtually all aerobic organisms, yet its dysregulation (iron overload or anemia) is a harbinger of many pathologic conditions. Hence, iron homeostasis is tightly regulated to prevent the generation of catalytic iron (CI) which can damage cellular biomolecules. In this study, we investigated the role of iron-binding/trafficking innate immune protein, lipocalin 2 (Lcn2, aka siderocalin) on iron and CI homeostasis using Lcn2 knockout (KO) mice and their WT littermates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 71 publications
0
28
0
Order By: Relevance
“…Lcn2 primarily controls the gut bacterial overgrowth by limiting its iron uptake and also mediates facilitation of the hypoferremia during inflammation 12 . Additionally, Lcn2 serve as an indispensable factor for proper neutrophil migration, adhesion, and function 50 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lcn2 primarily controls the gut bacterial overgrowth by limiting its iron uptake and also mediates facilitation of the hypoferremia during inflammation 12 . Additionally, Lcn2 serve as an indispensable factor for proper neutrophil migration, adhesion, and function 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggested that the beneficial effects of Lactis Lcn2 could be potentially explained, at least in part, by the augmented survival or colonization ability of the probiotic L. lactis that express Lcn2. Nevertheless, we could not rule out the possibility that exogenous Lcn2 may also provide mucoprotective effects to the host via: (i) mitigating gut dysbiosis such as preventing the bloom of Enterobacteriaceae (e.g., E. coli ) 4, 10 , (ii) restricting luminal iron and the labile iron pool 12 , thus attenuating iron-induced oxidative stress, (iii) serving as an epithelial survival factor 52 and promote wound healing 53, 54 . Further prolonged survival may also enhance the generation of L. lactis derived soluble, effector molecules, which can diminish gut inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Total iron levels were estimated using a standard curve generated with the iron AA standard (Ricca Chemical Company). Serum TIBC and catalytic iron was analyzed as described in detail elsewhere [19, 20]. Transferrin saturation was calculated as serum total iron/TIBC × 100 [21].…”
Section: Methodsmentioning
confidence: 99%